Bahasa slang positif vs negatif pada gen z di Sumatera Barat - Amelia, Sonya Sri; Arimi, Sailal (Universitas Mulawarman, 2024)
The inventiveness of teenagers—including those in West Sumatra—is what leads to the diversity in language usage. Abbreviations and acronyms have a role in the creation of slang. The purpose of this study is to characterize the different types of slang, their definitions, and the variables that affect their usage or emergence. The research employs a descriptive qualitative methodology that involves the use of skilled listening and engagement strategies to collect data, as well as recording and note-taking tools. data reduction, data presentation, and conclusion-drawing are the steps in the data analysis process. The results of data analysis show that the use of slang by Gen Z in Padang City has two forms of slang, namely abbreviations and acronyms, slang with a positive meaning is 14 data, in general the slang is an abbreviation of several regional names, while slang with a negative meaning is 15. In general, slang is an abbreviation of the words sarcasm, insults, insults and ridicule. Factors in the use of slang by Gen Z in West Sumatra are social factors, and developments in the times that are increasingly developing, including being considered modern slang, and keeping up with current developments.